Pengaruh Perendaman Pada Saliva Buatan Selama 14 Hari Pada Glass Fiber Non Dental Dan Glass Fiber Dental Terhadap Perlekatan Bakteri Streptococcus Mutans - Zwista Yulia Dewi; Widjijono Widjijono; Erna Prawita Setyowati (Jurnal Material Kedokteran Gigi, 2017)
The material in the oral cavity will be coated by saliva. The humidity of material that is immersed in water will increase from time to time. Longer immersion time in water causes an increase in the absorption of water by a material. Non-dental glass fiber can be used as an alternative replacement for fiber glass dental. The advantages of dental glass fiberis widely available with reasonably priced. Fiber glass non dental commonly used as building materials and automotive. Streptococcus mutans bacteria have the ability to stick to the whole surface of the mouth, including dental materials. The purpose of this study is to determine the effect of dental glass fiber and non-dental glass fiber immersion in artificial saliva for 14 days to the adhesions of Streptococcus mutans bacteria.Fiber used in this study is E-glass fiber dental(Fibersplint, Polydentia SA, Switzerland), non-dental glass fiber A (LT, China), flowable composite (CharmFil Flow, Denkist, Korea) and silane coupling agent (Monobond S, Ivoclar Vivadent, Liechtenstein). Subjects were divided into three groups, each group consisting of 5 samples. Streptococcus mutans bacteria was planted in BHI media and calculated by plate count method. Results were analyzed using ANAVA. From the research it showed that the average dental glass fiber bacterial adhesions value was (953.4 ± 7.19), non-dental glass fiber(953.4 ± 7.19) while the composite resin without using fiber glass (848 ± 7.07). Statistical analysis showed a variable composition have a significant effect (p <0.05). The conclusion of this research that the alkali metal content in the fiber glass can affect the amount of bacteria Streptococcus mutans adhesions.